2007
DOI: 10.1093/jac/dkm407
|View full text |Cite
|
Sign up to set email alerts
|

Maggot excretions/secretions are differentially effective against biofilms of Staphylococcus aureus and Pseudomonas aeruginosa

Abstract: Maggot ES are differentially effective against biofilms of S. aureus and P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
96
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(106 citation statements)
references
References 37 publications
6
96
0
4
Order By: Relevance
“…van der Plas et al also reported biofilm reduction at concentrations up to 20 lg ES per well [22]. In our in vitro experiments, each maggot produced more than 1.8 lg ES per hour.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…van der Plas et al also reported biofilm reduction at concentrations up to 20 lg ES per well [22]. In our in vitro experiments, each maggot produced more than 1.8 lg ES per hour.…”
Section: Discussionsupporting
confidence: 67%
“…However, they found inhibition in the turbidimetric assay and concluded the antibacterial activity depends on the kind of experiment. The first report that described the possible activity of ES against biofilms of P. aeruginosa and S. aureus in in vitro experiments is the recently published paper by van der Plas et al [22].…”
Section: Discussionmentioning
confidence: 99%
“…Valachova et al (2014) identified the full-length cDNAs of five novel putative salivary proteases of L. sericata, three of them from the serine protease families which could play a significant role in debridement of wounds. Also, recent studies investigated the potentials of sterile L. sericata ES to prevent the formation and disrupt bacterial biofilms of S. aureus and P. aeruginosa (van der Plas et al, 2008). It was found that ES prevented and disrupted S. aureus biofilms immediately and enhanced the formation of P. aeruginosa biofilms for 10 h after incubation, and then it began to breakdown P. aeruginosa biofilms (van der Plas et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Maggot excretions/secretions (ES) antimicrobial components have been shown to disinfect wounds by destroying bacteria that often do not respond to commercially available antibiotics, such as methicillinresistant S. aureus (MRSA) (Bexfield et al, 2004). Furthermore, maggot ES inhibited the pro-inflammatory response of human neutrophils and monocytes in the wound healing process (van der Plas et al, 2007(van der Plas et al, , 2009a. These secretions contained factors that could break down and inhibit S. aureus and P. aeruginosa biofilms, which colonized wounds and protected harmful bacteria from both the host immune system and therapeutic antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that bacteria, such as Escherichia coli are consumed and then eradicated in the acidic midgut of L. sericata larvae (Robinson and Norwood, 1934;Greenberg, 1968;Mumcuoglu et al, 2001;Daeschlein et al, 2007) and that the externalised larval excretion/secretion (ES) can reduce the viability of a number of Gram-negative and Gram-positive organisms (Simmons, 1935;Thomas et al, 1999;Bexfield et al, 2004;Kerridge et al, 2005;Bexfield et al, 2008;Jaklic et al, 2008;van der Plas et al, 2008;Cazander et al, 2009a;Harris et al, 2009). …”
Section: Introductionmentioning
confidence: 99%